Pengaruh Lingkungan Kerja Terhadap Kinerja Karyawan Pada Bank Mayapada Salemba Jakarta - Falah, Muhamad Sidiq Dinur; Damayanti, Wiwit; Koto³, Deni Indra Purnama (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2025)
This study aims to analyze the effect of work environment on employee performance at Bank Mayapada Salemba Jakarta. A quantitative approach with a saturated sampling technique was used, involving 78 employees. Data analysis employed simple linear regression. The results show that the work environment has a positive and significant effect on employee performance, indicated by a regression equation of Y = 4.531 + 0.896X. The t-count value of 18.438 > t-table 1.665 with a significance level of <0.05 proves that the work environment significantly affects employee performance. Furthermore, the coefficient of determination (R²) is 0.817, meaning that 81.7% of employee performance variation can be explained by the work environment, while the remaining 18.3% is influenced by other factors not examined in this study. Keywords: Work Environment, Employee Performance, Regression Analysis